Single-cell analysis reveals shared adaptive responses across different types of podocyte injury - Yang, Liuxiao; Sun, Lijun; Liu, Wu; Rui, Hongliang; Dai, Haoran; Liu, Wenbin; Liu, Baoli (Frontiers in Immunology, 2025)
IntroductionPodocytes are essential for maintaining the structural and functional integrity of the glomerular filtration barrier. Their damage constitutes a common pathological basis for proteinuria and renal function deterioration in kidney diseases. Podocyte injury exhibits marked heterogeneity in etiology, pathogenic mechanisms, and phenotypic manifestations across distinct kidney diseases, leading to different renal outcomes. However, the molecular underpinnings remain limited. Consequently, single-cell RNA sequencing (scRNA-seq) enables deconstruction of renal cell states with unprecedented resolution.MethodsHere, we integrated 16 scRNA-seq samples of human kidney tissues, totaling 73,684 cells from healthy controls and patients with IgA nephropathy (IgAN), idiopathic membranous nephropathy (IMN), and acute kidney injury (AKI). We identified 11 major cell types and analyzed podocyte injury mechanisms among these diseases, as well as their crosstalk within the glomerular niche. Key molecules were confirmed using immunohistochemistry.ResultsOur analysis identified distinct podocyte injury mechanisms across diseases: HSPG2-mediated signaling from mesangial cells in IgAN, upregulation of extracellular matrix-related genes in IMN, and increased SPP1 signaling within glomeruli in AKI. Despite divergent triggers, podocytes mounted convergent adaptive responses characterized by initial structural disruption, a mitochondria-driven compensatory phase, and subsequent functional dysregulation via multiple stress pathways, culminating in irreversible damage.ConclusionTogether, our study reveals both the heterogeneous and shared adaptive responses of injured podocytes through single-cell RNA analysis, providing new insights into disease mechanisms and potential therapeutic targets.